Key Steps to Improve Agribusiness Competitiveness, Part I : Input and Output Markets - Walton, Tom; Grishin, Vadim (International Finance Corporation, Washington, DC, 2018)
Agriculture is central to emerging market economies. In Africa it accounts for as much as 65 percent of employment and 32 percent of output. Globally, two-thirds of the world’s poor - some 750 million people - work in rural areas. But as economies expand and production shifts to manufacturing and services, agriculture’s share of employment and gross domestic product (GDP) decreases. At the same time, the broader agribusiness industry - business activities performed from farm to fork - is playing a more important role in growth and development. In part I, the emphasis is on improved land rights, better regulation of input and output markets, and better access to seeds and fertilizer that are all critical to this transition.